Survivors of COVID-19 are at high risk of posttraumatic stress disorder - Shuiyuan Xiao; Dan Luo; Yang Xiao (BMC, 2020)
Abstract Posttraumatic stress disorder (PTSD) is a common mental disorder caused by major psychological trauma. It could result in serious distress and disability. Previous epidemic studies report high prevalence rates among people exposed to the trauma resulted from an infectious disease epidemic. While the control of the epidemic and care of patients with COVID-19 are still the dominant task of the whole world, this commentary calls for attention to early intervention and prevention of PTSD among huge numbers of COVID-19 survivors, their family members, health care professionals and other first-line helpers.